Public theology and preaching in Korean Protestant churches - Park, Sangyil Sam (Review and expositor, 2017)
This article surveys the positive roles and challenges Korean Protestant churches have had in history from a perspective of public theology and its relation to preaching. It argues that preaching is inherently related to public theology as it shapes Christians’ actions to fulfill the message of the kingdom of God in public space.